Prevalence of Drug Abuse among Student in the University of Benin, Nigeria - Mustafa-Shaibu, Maryam; Igbinoba-Ojo Iyayamwan, Omorovbiye (University of Nigeria Journal of Political Economy, 2022)
Drug abuse continues to be a major social problem among University undergraduate’s students, with physical and mental health complications. Despite the known risks that are associated with drugs abuse, students continue using these drugs. The study examines the prevalence of drug abuse amongst student in University of Benin ,It identify the factors that influence the consumption of drug abuse amongst the University of Benin students and to investigate the effects of drug abuse on student academic performance. The Differential Association Theory by Edwin Sutherland guided this study, whereas questionnaires were used to collect information from respondent. The sample sizes for the study were 200 respondents and were purposively selected. More so, the findings showed that majority of student’s abuse drug due to peer influence, academic related problems and one of the major reasons for drug abuse among the students was to be appreciated by friends and alcohol was said to be the most frequently abused drug followed by marijuana and cigarette. Addition to that, the rate of school or class attendance for students who involved in consumption of drugs was observed to be poor hence lead to low in academic performance.